Comparable Outcomes in Acquired Severe Aplastic Anemia Patients With Haploidentical Donor or Matched Related Donor Transplantation: A Retrospective Single-Center Experience - Wang, QingYun; Ren, HanYun; Liang, ZeYin; Liu, Wei; Yin, Yue; Wang, QingYa; Wang, Qian; Sun, YuHua; Xu, WeiLin; Qiu, ZhiXiang; Ou, JinPing; Han, Na; et al. (Frontiers in Medicine, 2022)
Clinical data in severe aplastic anemia (SAA) patients were retrospectively analyzed to evaluate the outcomes of haploidentical hematopoietic stem cell transplantation (HID-HSCT) with matched related sibiling hematopoietic stem cell transplantation (MSD-HSCT) in complications and survivals. Thirty consecutive patients were enrolled in the study with a median follow-up of 50 months (range 4, 141), and the median age of the patients was 21 years (range 3, 49). All the patients achieved myeloid engraftment in the two cohorts. The cumulative incidences of platelet engraftment were 95.5% and 100% in HID cohort and MSD cohort, respectively. The median time for neutrophil and platelet recovery was 11（range 9, 19）days and 15（range 10, 25）days in HID cohort, and 12（range 10, 19）days and 14（range 8, 25）days in MSD cohort. The cumulative incidences of grade Ⅱ-Ⅳ and grade Ⅲ-Ⅳ acute graft versus host disease (aGvHD) in HID cohort and in MSD cohort were 18.9% vs 14.3% (P=0.77) and 10.5% vs 0% (P=0.42), respectively. The cumulative incidences of chronic graft versus host disease (cGvHD) was 22.7% in HID cohort and 25.5% in MSD cohort (P=0.868). The 5-year overall survival (OS) rates and 5-year failure-free survival (FFS) rates in HID cohort and MSD cohort were 85.1% vs 87.5% (P=0.858)，80.3% vs 87.5% (P=0.635), respectively. The median time to achieve engraftment, cumulative incidence of aGvHD and cGvHD, and the 5-year OS rate and FFS rate were not significantly different between the two cohorts. We suggest that HID-HSCT might be a safety and effective option for SAA patients without a matched donor.